Usability Testing Analysis on Digital Wallet Applications to Measure User Satisfaction - Nur Mutia Eka Pusparani; Tyas Setiyorini; Frieyadie Frieyadie (Jurnal Riset Informatika, 2023)
One of the issues that users of digital wallet apps often face is slow loading, which can cause frustration and disrupt the user experience. In addition, lack of app responsiveness due to server errors is also a complaint of users, which can lower their trust in the app. Another problem is the difficulty in the login process, which can make it difficult for users to access the application. From these problems, it is necessary to conduct a "usability testing analysis on digital wallets to measure user satisfaction." a study evaluates user satisfaction using ShopeePay, Dana, and Ovo as digital wallets. In this study, TCR is used as an indicator to measure the level of user satisfaction, and the variables considered are Attractiveness, Understandability, Learnability, and Operability. The results show that ShopeePay has the highest TCR of 78.77%, followed by Ovo at 77.32% and Dana at 75.58%. Attractiveness factors affect user satisfaction in ShopeePay, while in Dana, Learnability and Attractiveness factors influence. In Ovo, Operability and Attractiveness factors affect user satisfaction, while Understandability and Learnability have no significant effect. The findings from this study provide valuable insights for digital wallet service providers to optimize the factors that influence user satisfaction. This can help increase the acceptance and utilization of digital wallets in the growing market.